Marketing communications: innovative approaches to their formation and application tools - Burdyak, Oleh; Бурдяк, Олег (Wydawnictwo Wyzszej Szkoly Gospodarki Krajowej w Kutnie., 2020)
In this article, the author analyzes the features of the formation of marketing communications in organizations and modern, innovative approaches; emphasizes that the innovative approach to communications is based on the idea of communication as a strategic resource of the organization, the main task of which is to ensure the harmonization and productivity of relationships within the organization and its free entry into the external communication space. This approach involves the development of new principles for building a communication system at all levels and stages of enterprise’s activities, in all areas – from the development of elements of the marketing mix to personnel changes. The author considers social media to be an integral part and tool of modern marketing communications, thanks to cooperation with which leading companies attract the attention of a significant number of new users and strengthen their achievements. Almost 3.5 billion internet users in the world use social media, and this figure continues to grow. It creates a great potential for marketers to attract attention of a wide and interested audience to their brand.
Keywords: marketing communications, marketing tools, social media, SMM